PENGAMBILAN KEPUTUSAN USAHA MANDIRI MAHASISWA DITINJAU DARI FAKTOR INTERNAL DAN EKSTERNAL - Irawati, Rina (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
This study aims to determine the decision of students to have independent business STIE Malangkucecwara Malang in terms of internal and external factors. The type of research is descriptive. The sample of this research is 54 students from class of 2013-2015. The results of the study prove that the majority of sex students have independent business in STIE Malangkucecwara Malang is a woman. Internal factors students have independent business based on risk-taking, internal locus of control, self-generated motivation, the need for freedom, and creative ideas. External factors that encourage students to have independent business are: the influence of role models, family and friends support, opportunities, life satisfaction, and education. The results of this study are supported by previous researches: Indarti, Nurul and Rokhima Rostiani (2008), Yulia, Wasa and Dwi Endah Kusrini (2010), Zulkifli (2011), Ifham, Ahmad and Avin Helmi (2011), and Chasbiansari, Dyas (2007).